TEACHER`S SOCIAL EMOTIONAL HEALTH AND RESILIENCE IN SLOVAKIA AND LATVIA DURING DISTANCE LEARNING SITUATION - Gajdošova, Eva; Svence, Guna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article brings the research results of the teachers´ social-emotional health and resilience in Slovak Republic and in Latvia during distance learning situation. The sample consisted of 800 teachers, 400 teachers from each country, who completed Social-Emotional Health Survey-Teachers (SEHS-T) and Resilience Scale (RS) during months of May through July 2021. The research results showed the highest covitality level of Slovak teachers in comparison with Latvian teachers (p ˂.001, r = .36). There was found a big difference in covitality  in the clue domain Belief in Self in favour of Slovak teachers (p ˂.001; r = .44), there were only average differences in other domains - Belief in Others, Emotional Competence, Engaged Living. Latvian teachers reached high scores in cognitive reappraisal and optimism (p ˂.001). There was statistical difference in the level of resilience between Slovak and Latvian samples (p ˂.001; r = .35).  Slovak teachers scored higher. But the teacher’s resilience in both countries had moderate level. Significant positive strong correlation was found between resilience and covitality in Slovak teachers rs = .76** and in Latvian teachers rs = .66**. Significant high and moderate positive correlations were found also between resilience and covitality domains.